Limited ilioinguinal approach for unstable pelvic fractures in children aged <3 years - C. Gonzalez-Cancino; M. Gonzalez (Trauma Case Reports)
Background: Pelvic fractures in pediatric trauma account for 0.5–1 % of total hospital admissions, whereas acetabular fracture occurs at a rate of one case per 100,000 children; the low presentation rate is due to its unique characteristics. Standardized management for this age group is impossible. Conservative treatment has been commonly used but surgical correction has gained popularity. The purpose of this study was to report the authors' experience using a limited ilioinguinal approach for unstable pelvic fracture in two toddlers. Methods: Description of case studies. Results: Herein, we describe the treatment of two patients: a male patient struck by a vehicle (aged 1 year and 7 months) and a female patient ejected from a motor vehicle (aged 2 years and 1 month). They sustained an unstable type IV fracture in the modified Torode and Zieg classification. Surgical treatment was performed using a limited ilioinguinal approach, and stabilization was achieved using 3.5-mm reconstruction plate. There were no iatrogenic nerve injuries or infection. The female patient had left hip dislocation 2 months post-surgery and was unfortunately lost to follow-up. The male patient achieved radiological bone union without discrepancy, with no loss of reduction or evidence of pain during the mean follow-up period of 18 months. Conclusion: Pelvic fracture in children is rare. Based on fracture patterns, surgical stabilization may be necessary to prevent major complications in the short, medium, or long term. The limited ilioinguinal approach was proven to be a viable alternative for managing unstable pelvic fracture in children aged <3 years with minimal blood lo and shorter operative time, allowing more anatomical and stable reduction.